1986
DOI: 10.1111/j.1365-2621.1986.tb13067.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and Selected Attributes of Pork Tenderloin Steaks Heated by Conventional, Convection, and Microwave Ovens to Two Internal Endpoint Temperatures

Abstract: Six treatment combinations for determination of cholesterol and selected quality attributes of pork tenderloin steaks were studied with three oven types (conventional, convection and microwave) and two internal endpoint temperatures (7 1 "C and 77°C). In general, pork tenderloin steaks heated in the microwave oven had lower evaporative loss and higher drip loss. Cholesterol (wet weight basis) of the pork steaks was not affected by oven type; however, heating to the higher internal endpoint temperature (77°C) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Microwaved chops displayed slightly higher values than other cooking methods. Prusa and Hughes (1986) also found that microwave-cooked pork tenderloin steaks contained more cholesterol than steaks heated in a conventional oven. These results were attributed to less cholesterol lost in the cook drip during the short heating period.…”
Section: Resultsmentioning
confidence: 92%
“…Microwaved chops displayed slightly higher values than other cooking methods. Prusa and Hughes (1986) also found that microwave-cooked pork tenderloin steaks contained more cholesterol than steaks heated in a conventional oven. These results were attributed to less cholesterol lost in the cook drip during the short heating period.…”
Section: Resultsmentioning
confidence: 92%
“…Although no difference (P>O.O5) existed in cholesterol level due to internal temperature, a slight progressive increase was observed with increased internal temperature. Previous reports (Prusa and Hughes, 1986;Rhee et al, 1982;Slover et al, 1987) indicated that cholesterol of meat was concentrated upon heating, primarily through the removal of water.…”
Section: Resultsmentioning
confidence: 94%
“…Rhee el al. (1982a,b) and Prusa and Hughes (1986) have reported an increase in cholesterol concentration due to cooking. The values obtained by these workers are similar to those found for uncooked and cooked muscle in this study.…”
Section: Resultsmentioning
confidence: 94%